LncRNA profiles from Notch signaling: Implications for clinical management and tumor microenvironment of colorectal cancer - Dang, Qin; Liu, Zaoqu; Liu, Yang; Wang, Wenkang; Yuan, Weitang; Sun, Zhenqiang; Liu, Lin; Wang, Chengzeng (Frontiers in Immunology, 2022)
The interplay between long non-coding RNAs (lncRNAs) and the Notch pathway involves a variety of malignancies. However, Notch-derived lncRNAs and their latent clinical significance remain elusive in colorectal cancer (CRC). In this study, we introduced a framwork that could screen Notch-derived lncRNAs (named “NLncer”) and ultimately identified 24 NLncers. To further explore the clinical significance of these NLncers, we performed LASSO and Cox regression in TCGA-CRC cohort (n =584), and then retained six lncRNAs tightly associated with prognosis. The final model (termed “NLncS”) was subsequently tested in GSE38832 (n =122), GSE39582 (n =573), and an in-house clinical cohort (n =115). Ultimately, our NLncS model could serve as an independent risk factor and afford a robust performance for assessing the prognosis of CRC patients. Additionally, patients with high NLncS risk scores were characterized by up-regulation of immune pathways, strong immunogenicity, abundant CD8 + T cell infiltration, and potentially higher response rates to CTLA4-blockers, which turns out suitable for immunotherapy. Aimed at globally observe the characteristics of high-risk patients, somatic mutation and methylation modification analysis provide us with evidence at the genomic and transcriptomic levels. To facilitate the clinical transformability, we mined deeply into the sensitive compounds targeting with high-risk individuals and identified dasatinib is a candidate agent for patients with high Notch risk score. In conclusion, our NLncS model is a promising biomarker for optimizing the clinical management of CRC patients.